THE NATURE OF CHINA AND TAIWAN CONFLICTING RELATIONS - Stošić, Sanja (The Policy of National Security, 2023)
The relations between China and Taiwan are widely considered as one of the most sensitive issues, especially nowadays, in the era of U.S.-China strategic competition. For China, Taiwan issue is one of the key security issues. Within the scope of the new geopolitical dynamics in the existing world order, the goal of this paper is to address questions related to the China’s-Taiwan policy as well as the U.S.-Taiwan policy, providing a comprehensive theoretical framework for understanding the nature of China-Taiwan tense relations. Starting from the premise that the changing policies with regard to China, Taiwan and the United States, are related with the emerging global power shift, as well as with the redefinition of national interests of all the parties involved, by using qualitative data analysis, in this paper we will try to rethink how do changes in U.S.-China policy and Taiwan’s-U.S. policy may be primary triggers of the Taiwan Strait conflict scenario.